Evaluation of Lactobacillus paracasei subsp. tolerans isolated from Jenyn`s sprat (Ramnogaster arcuata) as probiotic for juvenile rainbow trout Oncorhynchus mykiss (Walbaum, 1792). - Lopez Cazorla, Andrea Cecilia (2014)
A lactic acid bacterial strain, Lactobacillus paracasei subsp tolerans F2, isolated from the intestine of Ramnogaster arcuata, was evaluated as growth promoters in juvenile rainbow trout Oncorhynchus mykiss (Walbaum, 1972) farming. In addition, the safety of the strain was assessed according to the FAO recommendations. Strain F2 was susceptible to the most antibiotics tested and no evidence of hemolytic activity was found. When the strain of Lactobacillus paracasei subsp tolerans F2 was administered with food, no adverse effects on animal?s health were observed and fish biomass increased 12% more in treatment group than in the control one. Significant differences were detected in the specific growth rate and feed conversion ratio. In the group receiving Lactobacillus paracasei subsp tolerans F2-supplemented feed quantitative differences in the microbial composition of fish feces with respect to the control group were observed. An important decrease of fungi and enterobacteria was observed in the feces from treatment group, coincident with an increase of lactic acid bacteria. This result would indicate a change in the composition of the intestinal microbiota of fish treated with the putative probiotic. These results suggest that the strain of Lactobacillus paracasei subsp tolerans F2 has potential to be applied to improve the performance in rainbow trout farming.